Estudo da luminescência persistente em cerâmicas de Sr(1-y-z)BxAl(2-x)O4:Euy,Dyz sinterizadas a laser - Alves, Ylla Grasielle dos Santos (2015)
Materials that have light emission for a long period of time even after ceasing the excitation attract curiosity of scientists for a long time. This phenomenon is named persistent luminescence and it has obtained scientific and technological visibility due to its great potential of applications. Among the materials that present this phenomena, it can be cited the strontium aluminate (SrAl2O4) that, when doped or co-doped with rare earth ions, presents naked eye visible persistent luminescence. On the other hand, the boron addition in the SrAl2O4 lattice has been studied due to contribution onto optical and structural properties. Additionally, in order to optimize the physical and chemical properties of the ceramic materials, several synthesis and sintering methods have been used. Among these methods, the laser sintering technique, which a CO2 laser as used as the main heat source, has been presented as an important method for the sintering of ceramic materials. In this work, it was studied the boron influence about the physical properties, particularly on the optical and structural properties, in laser sintered Sr1-y-zBxAl2-xO4:Euy,Dyz (SABED) ceramics. The SABED powders synthesis was developed by the Pechini´s method and analysed by the differential thermal analysis, thermogravimetry and X-Ray diffraction techniques. The SABED ceramics showed good microstructural homogeneity and transparency of up to 50% when sintered at a density power of (3.1 + 0.3) W/mm2 for 30 s. In all the samples were observed a good naked eye visible luminescence intensity for up to 10 minutes, with a characteristic Eu2+ band emission (centered at 512 nm). It is important to note that throughout process was performed at open atmosphere. Finally, the boron addition contributed significantly to improve the microstructure, transparency and naked eye luminescence intensity.